A checklist of halacarid and hydrachnid mites (Acari, Halacaridae & Hydrachnidia) associated with sponges (Porifera) - Chatterjee, Tapas (Zootaxa, 2021)
A compilation of halacarid and hydrachnid mite species found associated with sponges has been carried out based on published records. Altogether 78 halacarid mites species belonging to 15 genera viz. Agaue (9 species), Agauopsis (7 species), Arhodeoporus (1 species), Atelopsalis (1 species), Bradyagaue (1 species), Copidognathus (27 species), Halacarellus (7 species), Halacaropsis (2 species), Halacarus (5 species), Lohmannella (3 species), Maracarus (3 species), Rhombognathides (3 species), Rhombognathus (4 species), Spongihalacarus (1 species), and Thalassarachna (4 species) are reported. Twenty-four hydrachnid mite species belonging to three families viz. Hygrobatidae (2 species), Unionicolidae (20 species) and Pontarachnidae (2 species) are included. Some species of Unionicolidae are mentioned as possible sponge-mite species. Further studies, emphasizing developmental studies of unionicolid mites to get better ideas about associations with freshwater sponges are needed. Molecular sequencing will reveal more cryptic species and improve the quality of re-descriptions of currently recognized species in these sponge associated mites.